Dual diagnosis of obsessive compulsive and compulsive buying disorders: Demographic, clinical, and psychiatric correlates - Kim, Hyoun S.; Hodgins, David C.; Torres, Albina R. [UNESP]; Fontenelle, Leonardo F.; do Rosário, Maria Conceição; de Mathis, Maria Alice; Ferrão, Ygor A.; Miguel, Euripedes C.; Tavares, Hermano (Elsevier, 2018)
Aim: The present research assessed the rates as well as the demographic, clinical, and psychiatric correlates associated with comorbid obsessive-compulsive disorder (OCD) and compulsive buying disorder (CBD). Method: Participants were drawn from a large (N = 993) multi-center study of people seeking treatment for their OCD. The diagnoses of psychiatric disorders were made using the Structured Clinical Interview for DSM by registered psychologists and psychiatrists. The clinical correlates, including the severity and presence of OCD symptoms and dimensions were assessed using psychometrically sound measures. Results: 75 (7.5%) participants met criteria for comorbid CBD. The results of binary logistic regression found that women were more likely to present with comorbid CBD, whereas being a student was a protective factor. The presence of hoarding dimension, poorer insight, social phobia, binge eating disorder, internet use disorder and kleptomania were significantly associated with comorbid CBD. Conclusion: The results suggest that individuals with a dual diagnosis of OCD and CBD may represent a unique clinical population that warrants tailored interventions. Specifically, they were more likely to present with other psychiatric disorders characterized by high levels of impulsivity and compulsivity. Targeting psychological mechanisms common to impulsivity-compulsivity disorders may enhance treatment utility in this dual-diagnosis population.